An Analysis of the Trade Barriers to the Chinese Cultural Trade - Jiang, Jingchen; Jiang, Yanqing (Journal of Asian Business Strategy, 2015)
Chinese cultural trade possesses great developing potential. However, the strengths of Chinese cultural trade are hindered by barriers either set by other countries or induced by inherent differences. Although it is impossible to completely eliminate the effects of such trade barriers, yet efforts can be made in improving product quality, reforming government policies, perfecting human resources and designing marketing strategies, in order to alleviate the negative impacts of trade barriers. Given the limited scope of the present study, there are still many other crucial factors that are left out of the discussion of this paper, such as the influence of treaties in the WTO and the relationship between China and other countries. However, the unrelenting endeavor of the Chinese government and Chinese companies is sure to be paid off and Chinese cultural trade will embrace a brighter future.